Necesidad de incorporar un inciso en el artículo innumerado 22 (147) del Código de la Niñez Y Adolescencia, que se notifique a la persona alimentante y no ha disponer el inmediato apremio personal, luego de conocer la liquidación - Garces Cascante, Horacio Arturo (2015)
This thesis is divided into four chapters which are divided into CHAPTER: We speak about the generalities of those eligible to receive alimony, with their respective concepts, the evolution of the same alimony, the primary components that make, as the agents involved in this investigation, its impact on our country, we will discuss the obligor, on which is a person, talk about the general principle of the right of children and their obligors. CHAPTER TWO: We will discuss the legal framework of Childhood and Adolescence in the Political Constitution of the Republic of Ecuador, the international conventions, manifest on the Organic Code of Childhood and Adolescence, its scope, first, its institutional regime, applied instruments, financing, information and enforcement, protection of the rights of children and the obligors, as its transitional provisions, and final, in the latter revealing most relevant concepts applicable in this Code, it also appears on the apprehension of the obligor, and nonpayment of food pensions and their trial with different laws, the study of law is seen compared in Chile, Colombia and Venezuela and ends with the need to reform the Organic Code children and Adolescents CHAPTER THREE: Explains field research, finding an analysis of interviews and surveys conducted in this research work, a case study on the subject as well as conclusions, recommendations verification of both general and specific, contrasting hypothesis, doctrinal and empirical normal code. CHAPTER FOUR: We will verify and appreciate the findings, recommendations and legal proposal put forward based on the study and development of this thesis